Footwear affects gearning in the musculo-skeletal system in running - Braunstein, B.; Preukschat, D.; Potthast, W.; Karamanidis, K.; Arampatzis, A.; Brüggemann, G. P. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to evaluate the impact of barefoot running on grass versus shod running regarding the effectivness of running mechanics. Fourteen male runners performed five valid running trials at 4.0m/s ± 0.2. Running kinetics and running kinematics were recorded for one barefoot and five shod conditions. The comparison of barefoot and shod running showed different effects concerning the gear ratio at the ankle and knee joint. Running with shoes showed mechanical advantages at the ankle joint in the first, second and fifth part of the ground reaction phase but caused disadvantages at the knee joint.